FORMATION OF SUSTAINABLE HUMAN CAPITAL IN UKRAINE’S RENEWABLE ENERGY SECTOR THROUGH THE SYNERGY BETWEEN EDUCATION AND BUSINESS - Oriekhova, Alvina; Khromushyna, Lyudmyla; Tkachenko, Victoriia (Current Problems of Sustainable Development, 2026)
Forming sustainable human capital in the renewable energy sector is a key priority for ensuring national security, Ukraine’s post-war recovery, and its integration into the European space. The effective development of innovative sectors requires bridging the skills gap and developing effective institutional mechanisms to retain talented specialists within the country. Contemporary labour market challenges and the decarbonisation of the economy demand flexible approaches to the development of specific «green» competencies. The aim of this article is to substantiate the theoretical and methodological foundations for building sustainable human capital in Ukraine’s renewable energy sector through the prism of synergy between education and business, as well as to develop practical recommendations for adapting leading global models for training and retaining highly qualified personnel. The article examines the theoretical aspects and characteristics of the transformation of the labour market under the influence of environmental trends. It considers the essence of sustainable human capital as a strategic asset. The architecture of institutional interaction between labour market actors has been examined, and the external and internal factors influencing professional adaptation processes have been identified. Adopting a systematic approach to the integration of the academic and business sectors helps to minimise the risks of labour shortages and «brain drain». The specific features of how classic global models of education-business synergy function have been identified through a comparative analysis of the German dual system, the Scandinavian «triple helix» and the American venture- certificate model. The role of tools for sustainable human resource management, corporate research hubs and micro-qualification programmes has been defined. The author has identified and substantiated the strategic vectors for implementing the author’s hybrid model in Ukraine, which envisages the creation of regional «Education – Green Business» clusters, the legalisation of flexible short-term courses, and the launch of joint research platforms. Practical actions in these areas will facilitate the capitalisation of knowledge, enable the rapid addressing of staff shortages, ensure swift adaptation to technological changes, and contribute to the achievement of the country’s long-term energy independence.
Keywords: human capital; sustainability; renewable energy; synergy; higher education institutions; innovative business; international experience